TINJAUAN HUKUM ISLAM TERHADAP ARISAN BERSYARAT (Studi Kasus di Kranggan Prajurit Kulon Mojokerto) - Nur Kartika Sari (Maliyah : Jurnal Hukum Bisnis Islam, 2015)
The focus of this study is the requirement of compulsory debt, and debt payments that should be paid more based on the existing provisions. The conditional lottery in RW 03 of housing complex of Gatoel Mojokerto is not appropriate with the Islamic law like debt obligation and additional money in debt payment that can be called Riba. In this case, it is a kind is Riba Nasi’ah because it talks about debt and the additional money in the debt payment. The foundation of this law has already been in Al-Qur’an and Al-Hadits that explain about the rule of imposed debt; this debt is given to the one who does not have any need, and also explain about the rule of Riba, and anything that should not be done by a Moslem. Besides, in the foundation of Qard, this lottery does not fulfill the requirement and the pillars of Qard, that is about ‘Aqid; a Muqrid should give the debt to the one who really need as a mean of helping. Based on the conclusion above, it is expected for the members of lottery should eliminate the additional money in the debt payment and the rule of the compulsory debt. Finally, for the society of Gatoel housing complex, especially for members of the lottery should be more selective to choose the activity whether it has benefit.